2020
DOI: 10.1016/j.redox.2020.101677
|View full text |Cite
|
Sign up to set email alerts
|

Formononetin ameliorates oxaliplatin-induced peripheral neuropathy via the KEAP1-NRF2-GSTP1 axis

Abstract: Management of oxaliplatin-induced peripheral neuropathy (OIPN) has proven challenging owing to the concern that any OIPN-preventing agents may also decrease the efficacy of the chemotherapeutic agent and fail to reverse established neuronal damage. Nevertheless, targeting redox signaling pathways constitutes a promising therapy in OIPN and we have previously demonstrated the protective role of nuclear factor erythroid-2 related factor 2 (NRF2) in this disorder. Here, we investigated the protective properties o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 55 publications
0
24
0
1
Order By: Relevance
“…It has been reported that activation of Nrf2/HO-1 signaling is in favor of enhancing cell survival upon chemotherapy [75]. What is noteworthy is that phytochemicals such as curcumin [76] and formononetin [77] induce Nrf2/HO-1 signaling in reducing toxicity of oxaliplatin against liver and brain cells. These studies clearly demonstrate that Nrf2 signaling is of importance for alleviation of chemotherapy-mediated side effects.…”
Section: Nrf2 In Protection and Chemoresistancementioning
confidence: 99%
“…It has been reported that activation of Nrf2/HO-1 signaling is in favor of enhancing cell survival upon chemotherapy [75]. What is noteworthy is that phytochemicals such as curcumin [76] and formononetin [77] induce Nrf2/HO-1 signaling in reducing toxicity of oxaliplatin against liver and brain cells. These studies clearly demonstrate that Nrf2 signaling is of importance for alleviation of chemotherapy-mediated side effects.…”
Section: Nrf2 In Protection and Chemoresistancementioning
confidence: 99%
“…These mechanisms include upregulation of antioxidant and detoxification enzymes, activation of drug efflux transporters, inhibition of drug-induced cellular apoptotic responses and induction of Nrf2-dependent proteasome activity ( Rojo de la Vega et al., 2018 ; Panieri et al., 2020 ). On the other hand, adverse events resulted from anticancer drugs could also be affected by Nrf2/Keap1 signaling in normal tissues ( Yarmohammadi et al., 2020 ; Fang et al., 2020 ). Due to the broad participation of Nrf2/Keap1 signaling in the metabolism of and cellular defense against anticancer drugs in both cancerous and normal cells, it is expected that more and more anticancer drugs would be identified to be sensitive to Nrf2/Keap1 signaling.…”
Section: Anticancer Drugs That Could Interact With Nrf2/keap1 Signaling Modulatorsmentioning
confidence: 99%
“…For instance, paeoniflorin exerts neuroprotective effect by attenuating oxidative stress through Nrf2 activation in diabetic peripheral neuropathy mice [ 24 ]. 6-Gingerol, cinnamic acid, and formononetin have been shown to play antioxidant and anti-inflammatory roles in several neurological diseases, such as ischemic brain damage, Alzheimer’s disease, and oxaliplatin-induced peripheral neuropathy [ 25 27 ]. Both KEGG pathway enrichment and network analyses predicted the PI3K-Akt and Toll-like receptor pathways as the key signalling pathways that mediate the protective effect of HGWD against PIPN (Fig.…”
Section: Discussionmentioning
confidence: 99%